Frontiers in colorectal disease : St. Mark's 150th anniversary international conference - Russell, R. C. G.; Thomson, James P. S. (Butterworths, 1986)
Frontiers in Colorectal Disease presents a compilation of articles from the international conference titled 'Frontiers in Colorectal Disease'. It discusses the aspects of functional disorders, neoplastic disease and inflammatory bowel disease. It addresses the practical management of a variety of disorders of the colon, rectum, and anus. Some of the topics covered in the book are the basis of functional intestinal symptoms; nervous control of the gut; physiological reactions of the gastrointestinal tract to stress; visceral pain; mechanisms of flatulence and diarrhoea; pathophysiology of const.